Containment of procedure-associated aerosols by an extractor tent: effect on nebulized drug particle dispersal. (April 2021) - Fennelly, M.; Keane, J.; Dolan, L.; Plant, B.J.; O'Connor, D.J.; Sodeau, J.R.; Prentice, M.B.
Summary: Background: Several medical procedures involving the respiratory tract are considered as 'aerosol-generating procedures'. Aerosols from these procedures may be inhaled by bystanders, and there are consequent concerns regarding the transmission of infection or, specific to nebulized therapy, secondary drug exposure. Aim: To assess the efficacy of a proprietary high-efficiency-particulate-air-filtering extractor tent on reducing the aerosol dispersal of nebulized bronchodilator drugs. Methods: The study was conducted in an unoccupied outpatient room at St. James's Hospital, Dublin, Ireland. A novel real-time, fluorescent particle counter, the Wideband Integrated Bioaerosol Sensor (WIBS), monitored room air continuously for 3 h. Baseline airborne particle count and count during nebulization of bronchodilator drug solutions were recorded. Findings: Nebulization within the tent prevented any increase over background level. Nebulization directly into room air resulted in mean fluorescent particle counts of 4.75 x 10 5 /m 3 and 4.21 x 10 5 /m 3 for Ventolin and Ipramol, respectively, representing more than 400-fold increases over mean background level. More than 99.3% of drug particles were <2 μm in diameter and therefore small enough to enter the lower respiratory tract. Conclusion: The extractor tent was completely effective for the prevention of airborne spread of drug particles of respirable size from nebulized therapy. This suggests that extractor tents of this type would be efficacious for the prevention of airborne infection from aerosol-generating procedures during the COVID-19 pandemic.